The Impact of Carbon Footprints and Restoration Efforts on Temples Using Andesite Stone Materials - Herlambang, Rudy; Purwasito, Andrik; Warto, Warto; Widayat, Rahmanu (Research Horizon, 2023)
The various carbon footprints present in the environment can inevitably have a significant impact on cultural heritage sites. In fact, preserving cultural heritage buildings, including those made of andesite stone, is of paramount importance. This research aims to provide a clear understanding of the impact of carbon footprints generated by the degradation of temple buildings constructed with andesite stone. It also examines several strategies for restoring these structures as part of the broader effort to safeguard cultural heritage sites. The study's results indicate that the carbon footprint has resulted in the release of various chemical gases that have adversely affected the andesite stone, leading to structural issues. To address this, restoration efforts can be implemented through the establishment of a drainage system to control temple humidity and the improvement of concrete slabs to strengthen the temple foundations, which have eroded due to the impact of carbon footprints.